Engaging with academic and institutional changes: physical education and sport pedagogy's interest and ability to 'survive and thrive'. Issue 8 (12th October 2020) - MacPhail, Ann; Schaefer, Lee
ABSTRACT: Acknowledging differences in contexts, the purpose of this paper considers how physical education and sport pedagogy (PESP), while maintaining our collective identity, can most effectively develop a capacity to engage with academic and institutional changes in productive, proactive ways. This, we contend, entails considering extending the groups or communities in which PESP is represented to increase the potential to access substructures with other academic communities. We have chosen a metaphor to frame this work, acknowledging that metaphor can often open-up new ways to view a specific aspect or phenomenon that has been conceived in a common, or perhaps static way. Worked examples of the metaphor are presented from an Irish and Canadian perspective and implications of these examples pose possible ways forward.